2023
DOI: 10.1021/acschemneuro.2c00783
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elucidation of Ivermectin Binding to α7nAChR and the Induced Channel Desensitization

Abstract: The α7 nicotinic acetylcholine receptor (α7nAChR) mediates signaling in the central nervous system and cholinergic anti-inflammatory pathways. Ivermectin is a positive allosteric modulator of a full-length α7nAChR and an agonist of the α7nAChR construct containing transmembrane (TMD) and intracellular (ICD) domains, but structural insights of the binding have not previously been determined. Here, combining nuclear magnetic resonance as a primary experimental tool with Rosetta comparative modeling and molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…An initial blind docking of ligand 6 revealed a preference of the docking poses for the interface between the transmembrane domains of each chain (Supplementary Figure S21). This is consistent with the site reported for PNU-120596 in α7 nAChR, and the binding site of ivermectin in both the C. elegans glutamate-gated chloride channel GluClα and α7 nAChR. This site was then selected for targeted docking, and the centroid of the best five clusters was used as a starting point for molecular dynamics (3 × 500 ns) simulations. After the simulations, the best conformation was selected by root mean square deviation (RMSD) based clustering of the ligand heavy atoms (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An initial blind docking of ligand 6 revealed a preference of the docking poses for the interface between the transmembrane domains of each chain (Supplementary Figure S21). This is consistent with the site reported for PNU-120596 in α7 nAChR, and the binding site of ivermectin in both the C. elegans glutamate-gated chloride channel GluClα and α7 nAChR. This site was then selected for targeted docking, and the centroid of the best five clusters was used as a starting point for molecular dynamics (3 × 500 ns) simulations. After the simulations, the best conformation was selected by root mean square deviation (RMSD) based clustering of the ligand heavy atoms (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the side group of the ligand interacts with Pro240, Leu243, and Ile244 of the (−) M1, with Thr273 and Met276 of the (+) M2, and Ala298, Met301, and Ile302 (Supplementary Figure S22B). Of these interactions, some can be highlighted for their reported importance: Met276 being an amino acid previously reported as critical for the function of other allosteric modulators such as ivermectin and PNU-120596, , Leu277 being one of the hydrophobic constriction sites in the receptor pore lining, and Ala280 being one of the amino acid that interacts with the β1−β2 loop after it pivots during activation . The importance of the interactions between the protein and the ligand side group is highlighted by the functional results which showed that smaller substituents, like the bromide in the ligand 5 , fail to potentiate the response, and more polar substituents such as the alcohol group in ligands 8 and 9 have much weaker allosteric effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to the large radius of gyration (∼60 Å) of a PICK1 dimer, 57 which significantly exceeds the gap between two adjacent subunits of the ICD. 16,40 A future structural study involving α7 nAChR with full-length PICK1, encompassing both the PDZ and BAR domains, may provide additional insights into the interplay between these two proteins.…”
Section: ■ Resultsmentioning
confidence: 99%